Investigating discourse markers “you know” and “I mean” in mediatized English political interviews: a corpus-based comparative study - Fu, Yanli; Afzaal, Muhammad; El-Dakhs, Dina Abdel Salam (Frontiers in Communication, 2024)
This study employs a corpus-based approach to examine and compare how two discourse markers (DMs), namely "you know" and "I mean", are used within the context of two mediatised English political interviews. The analysis encompasses an exploration of the frequencies, functions, co-occurrences, and positional distributions of these two DMs. The study uses two specialized corpora consisting of interviews from two English political interview programs. The frequency analysis reveals that "you know" exhibits a statistically higher prevalence than "I mean" in both political interview programs, thereby reflecting the characteristics of political interviews. Moreover, it becomes evident that the Chinese interviewer (IR) makes more extensive use of "you know" compared to the British IR, while the British IR employs the DM "I mean" to a slightly greater extent than the Chinese IR. The functional analysis uncovers the multifaceted nature of these two DMs, as they fulfil diverse functions spanning various domains. It is observed that "you know" tends to be positioned medially within the discourse, while "I mean" predominantly appears in initial positions. These results highlight the distinctive interviewing styles employed by the two IRs, as reflected in their utilization of these two DMs. Finally, this research underscores the pivotal role played by these two DMs in serving a spectrum of communicative functions within the realm of political interviews, offering valuable insights into the interviewer's perspective.